The effect and clinical significance of FN1 expression on biological functions of gastric cancer cells - Zhou, Yuan; Cao, Guangxin; Cai, Hongyu; Huang, Haijing; Zhu, Xinguo (Cellular and Molecular Biology, 2020)
Fibronectin 1 (FN1) is a glycoprotein molecule widely distributed in cell structures such as smooth muscle cell layer, vascular cell membrane and nerve cell layer. It participates in cell adhesion, migration and movement of various cells. In recent years, FN1 has been shown to play an important role in the regulation of various malignant tumors such as lung cancer, colorectal cancer, and ovarian cancer. However, its regulation and mechanism of action in gastric cancer have been rarely reported, and these are also associated with some controversy. The aim of this study was to investigate the clinical significance of FN1 in gastric cancer, to study the effects of FN1 on proliferation, apoptosis, migration and invasion of GC cells, and the mechanisms involved. The expression of FN1 in gastric cancer tissues was determined using immunohistochemistry staining. The comparative expression levels of FN1 were assayed with RT-PCR and Western blotting. The correlation amongst FN1 expression, clinicopathological parameters and prognosis of gastric cancer patients was determined. Cell transfection was used to silenceFN1 expression in gastric cancer cells. Plate cloning and CCK-8 assays were used to determine cell proliferation, while apoptosis was assayed with flow cytometry. Cell migration and invasion was measured with transwell assay. The expressions of EMT-related proteins were assayed using western blotting. The results showed that FN1 was upregulated in GC tissues and cell lines, and its expression level was closely related to tumor invasion, TNM stage, lymph node metastasis and survival. Inhibition of FN1 expression significantly reduced proliferation, migration, invasion and EMT processes of GC cells, and enhanced cell apoptosis. These results confirm that FN1 is up-regulated in GC, thereby functioning as an oncogenic gene. The high expression of FN1 might affect the clinicopathological parameters and prognosis of gastric cancer patients.